The Hierarchy of Countries in the Contemporary Art World and Market.: An Empirical Survey of the Globalization of the Visual Arts - Quemin, Alain (Österreichische Zeitschrift für Geschichtswissenschaften, 2006)
Although studies on globalisation have multiplied since the 1990s there are still rather few empirical sociological studies in this area of interest. Drawing upon the case of contemporary visual arts, this paper tries to highlight how discourses widespread within the art world on globalization, métissage and the abolition of boundaries are largely due to illusion. When objectifying the positions occupied by different countries in the artistic domain a very marked hierarchy becomes apparent. This hierarchy reveals that beyond the development of international exchange there subsist on the one hand a centre with well-defined outlines consisting of some Western countries (the United States and Germany taking the best places) and on the other hand a vast periphery, consisting of all the countries that do not belong to the first set.